Respuesta :
Answer:
Step-by-step explanation:
Input: 1, 2, 3, 4, 5
Output: -7, -9, -11, -13
To get the output you'd add -2 each time. -7+(-2) is -9. -9+(-2)=-11. -11+(-2)=-13. And because it keeps on increasing like this the n should be 5. Because the output keeps increasing by the same value the input should too. It's increasing by 1.
( not sure if this is what you wanted us to answer)
Answer:
- When the input is n then the output is - 5 - 2n
---------------------------
Using table, put the output values as a sequence:
- -7, -9, - 11, - 13, ...
We see the first term is -7 and the common difference is - 2.
The nth term would be:
- t(n) = - 7 + (- 2)(n - 1)
- t(n) = - 7 - 2n + 2
- t(n) = - 5 - 2n